Up‐regulation of hsa‐miR‐221‐3p induced by UVB affects proliferation and apoptosis of keratinocytes via Bcl‐xL/Bax pathway. Issue 4 (18th January 2021) - Tu, Yunhua; Wu, Wenjuan; Guo, Yanni; Lu, Fengyan; Li, Xing; Xu, Dan; Zou, Dandan; Tu, Ying; Chai, Yanjie; He, Li
Summary: Background: Chronic actinic dermatitis (CAD) is a photoallergic skin disease with abnormal hyperplasia. At present, the mechanism of abnormal proliferation is not clear. Objective: To explore possible mechanism of CAD proliferative lesions. Methods: Immunohistochemistry (IHC) assay and small RNA sequencing were carried out. Quantitative real‐time PCR (qRT‐PCR) analysis was performed to evaluate expression levels of hsa‐miR‐221‐3p and FOS. The interaction between hsa‐miR‐221‐3p and FOS was identified by dual‐luciferase reporter assay. Expression of hsa‐miR‐221‐3p also was detected by qRT‐PCR after UVB irradiation. Influences of hsa‐miR‐221‐3p and FOS on cell viability and apoptosis were assessed through a series of functional experiments and rescue experiments. Western blot analysis was used to detect protein expression of fos, Bax, Bcl‐xL, and caspase‐3. Results: Patients with CAD had marked epidermal hyperplasia. The expression of hsa‐miR‐221‐3p was up‐regulated in CAD while FOS was significantly down‐regulated. Dual‐luciferase reporter assay confirmed that hsa‐miR‐221‐3p targeted FOS 3'UTR. Hsa‐miR‐221‐3p induced by UVB ranged from 0 to 30 mJ. Moreover, hsa‐miR‐221‐3p overexpression or FOS knockdown promoted cell proliferation and reduced cell apoptosis. Western blot showed that hsa‐miR‐221‐3p negatively regulated fos, which regulated Bcl‐xL/Bax. Cell proliferation caused by hsa‐miR‐221‐3p overexpression or FOS knockdown could be reversed by Bcl‐xL inhibitor. Conclusion: Hsa‐miR‐221‐3p induced by UVB targeted FOS 3′UTR, which played an important role in regulating proliferation and apoptosis of keratinocytes via Bcl‐xL/Bax pathway; this may provide a new insight for CAD proliferative lesions.